Efektivitas Self-hypnosis terhadap Depresi dan Kecemasan Pasien Pasca Seksio Sesarea: Randomized Controlled Trial - Fahma, Hilmia; Arfani Prawiragara, Fachrizal (Jurnal Kesehatan Islam : Islamic Health Journal, 2025)
Background: Depression and anxiety are common psychological problems experienced by post-cesarean section mothers, affecting maternal well-being and infant development. Non-pharmacological interventions such as self-hypnosis may serve as safe and effective therapeutic methods. Objective: To evaluate the effectiveness of self-hypnosis in reducing depression and anxiety in post-cesarean section patients. Methods: This double-blind randomized controlled trial used a pretest–posttest control group design with 32 respondents randomly assigned to an intervention group (self-hypnosis, 15 minutes, twice daily, for 14 days) or a control group (cesarean section educational recording). Depression was assessed using the Edinburgh Postnatal Depression Scale (EPDS) and anxiety using the Postpartum Specific Anxiety Scale (PSAS). Within-group analysis used paired t-test or Wilcoxon, and between-group analysis used independent t-test or Mann–Whitney. Results: The intervention group’s EPDS score significantly decreased from 12.25 ± 1.29 to 7.94 ± 1.39 (p=0.000), while the control group showed no significant change (12.00 ± 1.21 to 11.50 ± 1.41; p=0.083). PSAS scores in the intervention group significantly decreased from 91.50 ± 3.82 to 74.13 ± 3.52 (p=0.000), whereas the control group did not (90.88 ± 3.09 to 89.69 ± 3.22; p=0.083). Between-group differences in score reduction were significant (p=0.000). Conclusion: Self-hypnosis is effective in reducing depression and anxiety in post-cesarean section patients and can be considered a supportive non-pharmacological intervention. Keywords: self-hypnosis, postpartum depression, postpartum anxiety, cesarean section